On the Liouville integrability of Edelstein's reaction system in R3. (March 2018) - Ferragut, Antoni; Valls, Claudia; Wiuf, Carsten
Highlights: We consider Edelstein's dynamical system of three reversible reactions in R 3 and show that it is not Darboux nor Liouville integrable. To do so we characterize its polynomial first integrals, Darboux polynomials and exponential factors. Abstract: We consider Edelstein's dynamical system of three reversible reactions in R 3 and show that it is not Liouville (hence also not Darboux) integrable. To do so, we characterize its polynomial first integrals, Darboux polynomials and exponential factors.